Conceptual tourism analysis: towards your ontological vision - Castañeda, Esteban Arias (Revista Turismo em Análise, 2019)
This research work with a view to essay, has the aim of propose a reflexive vision of tourism, through the analysis of its concept, so that it orients its meaning towards the interpretation of the phenomenon. The methodology used for this research is of a qualitative nature, in which the hermeneutical method served to study various tourism concepts and their disciplinary perspective, to thereby understand their conceptual reality and present an ontological position of this human movement. Before analyzing the concepts, it is necessary to differentiate the two worlds of tourism: ontic and ontological, which, by the way, present in life itself. The first of these is the one that allows this exercise, real, objective, to make it an object of study, aware of itself. In the second case, the ontological part of tourism occurs without taking into account the thing, it is the traveling and primitive instinct of the human being; of its original sense, idle and wandering by nature. Here he wonders about the being of Tourism. As a conclusion, the concept should refer to the human possibility of moving voluntarily and returning to its origin. As it is a human phenomenon, the use of tourist services would seem irrelevant.